2020
DOI: 10.1080/01652176.2020.1759844
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function and glucose metabolism in overweight and obese cats

Abstract: Background: In people, obesity and prediabetes mellitus might predispose to chronic kidney disease (CKD). Aims: To assess the association of overweight [Body condition score (BCS) >5] and glucose metabolism alterations, with established or potential markers of CKD. In addition, fructosamine and fasted blood glucose were compared as predictors of early abnormal glucose metabolism. Methods: 54 clinically healthy cats were included in a cross-sectional study comprising 25 neutered males and 29 (28 neutered) femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Neither did these markers differ between cats with BCS = 5 and cats with BCS > 5. Therefore, the results of this prospective study add to previous reports that suggest that overweight does not have a relevant influence on kidney function in healthy cats (Greene et al., 2014 ; Pérez‐López et al., 2019 ). A retrospective, epidemiological study reported that, after ruling out dehydration, cats with greater body weight were less likely to develop CKD (Greene et al., 2014 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Neither did these markers differ between cats with BCS = 5 and cats with BCS > 5. Therefore, the results of this prospective study add to previous reports that suggest that overweight does not have a relevant influence on kidney function in healthy cats (Greene et al., 2014 ; Pérez‐López et al., 2019 ). A retrospective, epidemiological study reported that, after ruling out dehydration, cats with greater body weight were less likely to develop CKD (Greene et al., 2014 ).…”
Section: Discussionsupporting
confidence: 78%
“…The owners participated voluntarily after signing an informed consent form. Exclusion and inclusion criteria were the same as described previously in a cross‐sectional study undertaken with the same animals (Pérez‐López et al., 2019 ). Briefly, cats with CKD, diabetes or other disorders were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger, more extensive study. 14 This study was approved by the Animal Welfare Ethics Committee, ULPGC, Spain (reference number 10/2018). Cats were recruited after owners voluntarily signed an informed consent form.…”
Section: Selection Of Animals and Study Designmentioning
confidence: 99%
“…Those correlations emerged only after adjustment for ppBMI, which could be explained by the fact that ppBMI influences this association, as previously seen by a group of non-pregnant participants [ 57 ]. After accounting for albumin, the significance of the observed associations was lost, which has already been observed in overweight and obese animal models [ 59 ]. Finally, it should be noted that much weaker correlations were observed between fasting glucose and fructosamine levels than between markers of insulin resistance and fructosamine levels.…”
Section: Discussionmentioning
confidence: 99%